Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan, dan Ukuran Perusahaan Terhadap Ekuitas Perusahaan Jasa Keuangan di Indonesia - Rizka Dwi Dayanti (2021)
This study aims to analyze the effect of tax planning, deferred tax expense, and firm size on equity. This study is a quantitative study with secondary data that obtained a sample of 89 financial sector companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The analysis techniques used classical assumption test, regression model test, multiple linear regression, and hypothesis test. From the results of analysis, it can be concluded that (1) tax planning has no effect on equity, (2) deferred tax expense has no effect on equity, (3) firm size has a positive significant effect on equity.